Between Ordinary Harm and Deviance: Evaluating the UK’s Regulatory Regime For Controlling Air Pollution From Wood Burning Stoves - Heydon, James (The British journal of criminology, 2023)
Particulate matter (PM) in air pollution causes illness, injury and premature death by infiltrating essential organs. Wood burning stoves are a primary source of PM in the United Kingdom, where domestic wood burning emissions have tripled over the last decade. This article adopts a constructivist lens to examine the regulatory regime controlling these pollutants. Combining analysis of ‘expert’ interviews, responses to Freedom of Information requests and government records exempting appliances from Smoke Control Area rules, it illustrates how efforts at controlling ‘smoke’ in the past have become instrumental in encouraging the production of PM from stoves in the present. In doing so, this article demonstrates the utility of research sensitive to processes underpinning the (non)construction of environmental issues as deviant and suggests a lens through which ordinary harms can be better understood.